Study the Integrated Nursing Supervision Process in Clinics Based on the Recognition of Professional Nurses in Private Hospitals - Sanprasan, Penchun; Kulpakdee, Rungnapa; Wonganantnont, Pattariga (Journal of The Royal Thai Army Nurses, 2020)
This research was an integrated research which aimed to study the clinical integrating of nursing supervision process according to the perceived by professional nurses in private hospitals. Data collecting was done by using the questionnaires to inquire the opinion of the private professional nurses and in-depth interview. The purpose of this paper was to study the behavioral in clinical integrating of nursing supervision process according to the perception of the professional nurses and the nurse population those who work among the private hospitals around Bangkok and Metropolitan area. Primarily, the focus was on the supervision of nursing quality assurance. The Secondary focus was on the process of contribution and learning respectively. In accordance with the quality research, it found that learning on the supervision had many related factors either the preparation of supervisors, supervision issues or the supervision technique which needed to be developed. Such a personal factor as work experiences had a negative correlation with the clinical integrating of nursing supervision process according to the perception of the professional nurses amongst the private hospitals. The integrated nursing supervision significance was on the nurses who had much work experience, and vice versa.